PENGAMBILAN KEPUTUSAN PENILAIAN KINERJA PEGAWAI DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA PT. SMART SOLUTION - Cahyadi, Cepi; Simarangkir, Manase Sahat H; Jaelani, Rusani (Jurnal Inkofar, 2023)
The quality of human resources is one of the factors to increase the productivity of a company's performance, so companies need to assess employee performance to find out how they are carrying out their duties. Problems that occur at PT. Smart Solution Bekasi is an employee performance assessment process that is carried out subjectively so that it is still difficult to determine the best employee performance. The AHP (Analytical Hierarchy Process) method is used as a support for decision making which can simplify an existing problem so that it can speed up the decision making process. Based on the results of the calculation process that has been carried out using the Analytical Hierarchy Process method, it is obtained that the priority order of the main criteria in selecting employee performance appraisals is the attendance criterion with a value of 0.6169, in second place is the speed criterion with a value of 0.0564 and in third place is the tardiness criterion with a value of 0.0554 as well as for fourth place is the work results criterion with a value of 0.2703.Keywords : Decision Support System, Analytical Hierarchy Process